A complete energetic and exergetic analysis of a solar powered trigeneration system with two novel organic Rankine cycle (ORC) configurations. (25th January 2021) - Jafary, Shirko; Khalilarya, Shahram; Shawabkeh, Ali; Wae-hayee, Makatar; Hashemian, Mehran
Abstract: Present study aims to compare two solar powered trigeneration systems from energetic and exergetic viewpoints. Said systems are consists of three different sub-systems including solar energy (as a prime mover), Organic Rankine Cycle (ORC), and double-effect absorption chiller. In one of the proposed trigeneration systems Internal Heat Exchanger (IHE) has been used in the configuration of ORC (ORC-IHE). However, in the other system the mixture heater has been included in the configuration of ORC to make Regeneration Organic Rankine Cycle (RORC). Difference between these two systems is related to ORC unit so that one of the cycles is associated with an Internal Heat Exchanger (ORC-IHE) and the other is equipped with mixture heater to make Regeneration Organic Rankine Cycle (RORC). Understanding the changes in the behavior of each component or cycle simultaneously can open new horizons which can be taken as the added-value of this research. The thermodynamic simulation of the proposed models was done by EES software. The prime mover of both ORCs is the solar power plant with parabolic through collectors (PTC). Forasmuch including/excluding any component to/from one of sub-systems affects the overall performance of system it is essential to have an elaborate comparison between these two systems with such unique configurations. To this end, the effect of several decisive parameters including turbine inlet pressure (outlet form evaporator) Pave and condenser pressure on the energetic and exergetic efficiency of net power, heating and cooling production of system was explored. Interestingly, it was turned out that the energy and exergy efficiency of ORC-IHE configuration in the proposed trigeneration system outweighs RORC configuration. Results revealed that the overall energy efficiency of the ORC-IHE-based system and RORC-based system are 93.35% and 86.66% respectively. Accordingly, the overall exergy efficiency for ORC-IHE-based system and RORC-based system are 12.69% and 6.641% respectively.